Who Secures Women’s Capabilities in Martha Nussbaum’s Quest for Social Justice - Basu, Amrita (Columbia Journal of Gender and Law, 2010)
Among the many issues that feminists have debated, three stand out for their urgency and significance: the relationship of theory to practice, universalism to particularism, and the transnational to the local and national. Feminism as theory continues to have a complicated and vexed relationship to women’s activism. Even women who engage in struggles that observers might term feminist do not necessarily share feminist identities or participate in women’s movements. Similarly, feminists continue to be troubled by universalism. Although certain forms of universalism are integral to most feminisms, Western feminist universalism has been presumptuous in condemning non-Western practices with scant understanding of the cultural and historical contexts which give them meaning. Feminist movements in the global South have sometimes been undermined by Western funded projects which have narrowed the agendas and constituencies of women’s movements and by hegemonic Western feminists’ appropriation of local discourses. As I elaborate below, I believe that debates about global feminisms have influenced Nussbaum’s work and its reception. I begin by describing the key tenets of the human capabilities approach and show how it represents an advance over human rights. I then place capabilities in the context of women’s movements transnationally. I assess the different ways in which national states and transnational organizations impede and support the recognition of capabilities. I argue that social movements have a critical role to play in determining and realizing capabilities.